Effect of increasing dosis of KNO3 on the growth of citrus rootstocks seedlings - de Carvalho, Sérgio Alves (Pesquisa Agropecuaria Brasileira, 1994)
Seeds of rangpur lime (Citrus limonia Osbeck) and Sunki mandarin (Citrus sunki Hort. ex. Tanaka) were germinated in trays of expanded polyestyrene, compound by 128 pyramidal cells holding about 75 ml of composed vermiculite and pinus rind, plus 500 ppm of P2O5. In a randomized experimental design and using 32 plants per plot in four replications for each rootstock, the dosages of 0,0; 0,1; 0,2 and 0,3% of KNO3 were tested, applied weekley. At 150 days after sowing, the plants were withdrawn from the trays for the determination of height, stem diameter at 1 cm from the colum and dry matter weight of the shoots and of the roots. The analysis of the data reveals, for both rootstocks, that the employment of increasing dosis of KNO3 caused linear additions of the obtained values for all the evaluated growth characteristics, having the rangpur lime shown the greatest growth vigor then the sunki mandarin, independently of the treatments with the nitrogen fertilizer.